Core temperature changes and sprint performance of elite female soccer players after a 15-minute warm-up in a hot- humid environment - Somboonwong, J.; Chutimakul, L.; Sanguanrungsirikul, S. (The Journal of Strength and Conditioning Research, 2015)
Warm-up session should be modified according to the environmental conditions. However, there is limited evidence regarding the proper soccer warm-up time for female players in the heat. The purpose of this study was to examine the rise in core body temperature and the sprint performance after a 15-minute warm-up in a hot-humid environment using female soccer players during the different phases of their menstrual cycle. Thirteen eumenorrheic national female soccer players (aged 18.8 ± 1.3 years, VO2max 53.05 ± 6.66 ml/kg/min) performed a 15-minute warm-up protocol at an ambient temperature of 32.5 ± 1.6° C with a relative humidity of 53.6 ± 10.2% during their early follicular and midluteal phases of their cycle. The warm-up protocol is composed of jogging, skipping by moving the legs in various directions, and sprinting alternated with jogging, followed by a 45-minute recovery period. Rectal temperatures were recorded during the rest period and every 5 minutes throughout the warm-up and recovery phases of the study. Heart rate was monitored at rest and every 5 minutes during the warm-up. Forty-yard sprint time was assessed immediately after the completion of warm-up, which was later compared with the time at baseline. The value for the baseline was obtained at least 2 days before the experiment. During the early follicular and midluteal phases, the rectal temperatures obtained at the end of the warm-up period were significantly (p < 0.05) higher by 1.26° C (95% confidence interval [CI] = +0.46 to +2.06° C) and 1.18° C (95% CI = +0.53 to +1.83° C), whereas the heart rates increased to 153.67 ± 20.34 and 158.38 ± 15.19 b/min, respectively. After 20 minutes of the recovery period, the rectal temperature decreased by approximately 50%. The sprint times were significantly (p < 0.05) faster post-warm-up during both the early follicular (5.52 seconds; 95% CI = 5.43-5.60 seconds) and midluteal phases (5.51 seconds; 95% CI = 5.41-5.60 seconds) compared with the baseline time (5.66 seconds; 95% CI = 5.58-5.74 seconds). There were no significant differences in any parameters assessed after warm-up between the 2 phases. In conclusion, a 15-minute warm-up increased the core temperature by approximately 1° C and improved the 40-yd sprint time for elite female soccer players in a hot environment regardless of menstrual phase.